Participatory-Based Character Education: Indonesian School Children’s Experiences - Muassomah, Muassomah; Yaacob, Salmy Edawati; Khairiah, Khairiah; Yurisa, Penny Respati; Demina, Demina (Jurnal Ilmiah Peuradeun, 2025)
Character education has been subjected to a top-down approach with a student center system. The values embedded completely come from the teachers or the school. This study explored how the participatory learning model could effectively instill character values in students. Students are given space to be involved and subjected to a series of character education processes. It aims to describe how students’ and teachers’ participation could compile the points of character values, how students apply the learning materials designed together, and how they are involved in providing evaluations for themselves and their friends. The qualitative descriptive method was employed in the current study. It aimed to observe and listen to the stories of students and teachers regarding their involvement in the process of curriculum development. Documentation on the learning modules was made for data collection. The data were taken by considering the representation of students and teachers. They engaged in every pulse of the learning process, which led to cognitive and affective development. The research proposed a cooperative investigation alongside other educational institutions, factoring in both the type and affiliation of these schools, aiming to produce more diverse and well-rounded outcomes.